SECONDARY DATA ANALYSIS OF PARTIAL PRODUCTIVITY INDEX TO DETERMINE QUALITY OF SCHOOL - Rinawati, Anita; Mutrofin, Mutrofin (Lembaran Ilmu Kependidikan, 2014)
Is not an easy thing to select Senior High School (SMA).The new students recieving  programme hold before new academic year in July make the parents of students who have just graduated from Junior High School confused. Generally, the reason  to select favourite school is based on a wrong public opinion. Selecting Senior High School (SMA) is supposed to rely on the quality of Instructional  work. One of Indicators of the instructional  work quality is a productivity level. This research aims to reveal partial productivity index of Senior High Schools (SMA)  located in Jember City and sequence them in top ten category. This research belongs to descriptive research which emphasizes on two things. The first emphasis   is on the final score of national examination (NEM) obtained by  Junior high School Students who graduated in academic year of  2011/2012 as the input while the second is the final score of national examination obtained by Senior high School (SMA) students who graduated  in 2013 as the output. The analysis is meant to find out the comparation result index betwen input and output score. The research result shows that 10 of 15 Senior High Schools located in Jember City have productivity level around 68,33%  up to 98,46%.